1958
DOI: 10.1139/y58-036
|View full text |Cite
|
Sign up to set email alerts
|

Reticulo-Endothelial System Stimulating Compounds and Their Mechanism of Action

Abstract: A series of compounds are described which exhibit therapeutic activity in experimental tuberculosis, acting exclusively on the host. The active compounds (citronellyl acetate, d-limonen, linalyl acetate) induce a local India ink and trypan blue accumulation and also stimulate the macrophages in vitro and in vivo to an increased phagocytic activity. Sera of the animals treated with therapeutically active compounds stimulate the macrophages of normal animals to an increased phagocytosis. A correlation between ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Most of the volatile oils tested inhibited phagocytosis, although the mixture of bornyl and isobornyl acetates showed a mild stimulating activity (21.3%) at the highest concentration tested (55.90 μg/mL). Some authors have also found stimulatory effects on phagocytosis for a few essential oils, such as those of Rheum palmatum L. and Allium sativum L., and for some pure constituents, such as citronellyl acetate and linalyl acetate. ,, Essential oils from cajuput, tarragon, and coriander showed no activity whatsoever on phagocytosis at the concentrations tested.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Most of the volatile oils tested inhibited phagocytosis, although the mixture of bornyl and isobornyl acetates showed a mild stimulating activity (21.3%) at the highest concentration tested (55.90 μg/mL). Some authors have also found stimulatory effects on phagocytosis for a few essential oils, such as those of Rheum palmatum L. and Allium sativum L., and for some pure constituents, such as citronellyl acetate and linalyl acetate. ,, Essential oils from cajuput, tarragon, and coriander showed no activity whatsoever on phagocytosis at the concentrations tested.…”
Section: Resultsmentioning
confidence: 97%
“…Some authors have also found stimulatory effects on phagocytosis for a few essential oils, such as those of Rheum palmatum L. and Allium sativum L., and for some pure constituents, such as citronellyl acetate and linalyl acetate. 8,11,18 Essential oils from cajuput, tarragon, and coriander showed no activity whatsoever on phagocytosis at the concentrations tested.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations